Combined Ruxolitinib and Venetoclax Treatment in a Patient with a BCR-JAK2 Rearranged Myeloid Neoplasm. (28th July 2021) - Lap, Coen J.; Nassereddine, Samah; Liu, Min-Ling; Nava, Victor E.; Aggarwal, Anita
Abstract : Hematological malignancies with a BCR-JAK2 rearrangement have been described only sporadically in the literature over the last three decades. Although most patients suffer from a chronic myeloid neoplasm with marked eosinophilia, the clinical presentation varies significantly and can even manifest as a lymphoid malignancy. In this case report, we present a patient with a therapy-related BCR-JAK2 + myeloid neoplasm with extensive extramedullary disease localizing in the lymph nodes. While treatment with a JAK2 inhibitor (ruxolitinib) was not able to stop disease progression, combination treatment with inhibitors of both JAK2 and BCL2 (venetoclax) resulted in disease control for over 1.5 years. Combining these two inhibitors might be strategic in these patients, not only because BCL2 is a downstream target of JAK/STAT signaling but also because BCL2 is crucial for JAK2 inhibitor resistance. The recent inclusion of JAK2 -rearranged malignancies in major classification systems and guidelines emphasizes the importance of not only getting a better understanding of the clinical phenotype of these rare disorders but also of identifying alternative treatment options for patients ineligible for allogeneic stem cell transplantation. Considering the low toxicity of combination treatment with these two small molecule inhibitors, this regimen could be further explored in future studies.